THE DEGREE OF TEACHERS’ COMMITMENT TO THE CODE OF CONDUCT AND ETHICS OF PROFESSION AS PERCEIVED BY SCHOOLS PRINCIPALS AND EDUCATIONAL SUPERVISORS IN KARAK GOVERNORATE - A. H. Aldmour, Reyad (European Scientific Journal, ESJ, 2014)
This study aimed at determining the degree of teachers’ commitmentto the Code of Conduct and Ethics of Profession as Perceived by SchoolsPrincipals and Educational Supervisors in Karak Governorate. It aimed atidentifying the impact of the variables of gender, qualification, expertise, andprofession position on the degree of response by the sample members. Thesample consisted of 131 principals and 65 supervisors. The researcherdeveloped a questionnaire of 55 items. After it was verified in terms ofconfidence and stability, it was distributed over the sample, whichconstituted 50% of the study population. The study concluded some resultsmainly that the degree of teachers’ commitment to the code of conduct andethics of profession was medium as perceived by principals and supervisors.The results also showed that there were statistically significant differences(α≤0.05) attributed to the profession position for the favor of principals. Thestudy recommended enrichment of training programs, dedicated for teachers,by criteria included in the Code of Conduct and Ethics of Profession.